ReBase: Data acquisition and management system for neuromotor rehabilitation supported by virtual and augmented reality - Barbosa, Tiago Trotta Lara; De Paiva Guimarães, Marcelo; Brandão, Alexandre Fonseca; Da Rocha, Leonardo Chaves Dutra; Iope, Rogerio Luiz [UNESP]; Brega, José Remo Ferreira [UNESP]; Dias, Diego Roberto Colombo (Association for Computing Machinery (ACM), 2021)
There is great interest in developing virtual reality and augmented reality applications for use in neuromotor rehabilitation treatments. These applications provide the benefits of traditional rehabilitation without becoming tiresome. Furthermore, the way the users interact with these applications makes it possible to retrieve and analyze the data generated by their movements during treatment. However, it is hard to find datasets of body movements, and those available do not include specific movements in the rehabilitation context. We present a development framework for virtual and augmented reality applications to support neuromotor rehabilitation.
Keywords: Augmented reality; Database; Gesture recognition; Neurorehabilitation; Virtual reality